(Re)Constructing the Bengali: Propaganda and Resistance in Immediate Post-1971 Pakistani Fiction - Sen, Madhurima (SARE: Southeast Asian Review of English, 2023)
During the war of 1971 and for a considerable amount of time afterward, manipulation of media reports and military propaganda in Pakistan contributed to cultural stereotypes of Bengalis as ‘others’. This paper analyses two immediate Pakistani fictional responses to the war published in 1973: “Bingo” by Tariq Rahman and “Hearth and Home” by Parveen Sarwar. It considers the relationship between literature as a medium and the rigid structure of religious nationalist loyalties and state propaganda, probing the dynamics between imaginative fiction and the top-down approach of statist historiography. It draws attention to the heterogeneity of literary strategies employed by authors and their divergent engagements with formulaic images of the Bengali ‘other’, which in turn shape the construction of national identity in the narratives. Along with focusing on the role of literature in ‘shattering the silence’, it aims to foreground the role played by fiction in maintaining stereotypical, archetypal, and antagonistic inter-ethnic relations. Keywords: War, Othering, Religion, Nationalism, Propaganda, Resistance